ORGANISATIONAL POLITICS AND THEIR EFFECT ON WORKPLACE LEARNING - Cacciattolo, Karen (European Scientific Journal, ESJ, 2014)
The paper discusses the findings of the author‘s doctoral thesis of which results have identified a number of effects of political behaviour that hinder or support workplace learning. The work adds to knowledge since, whilst a small amount of literature exists regarding the relationship between organisational politics and learning, there is very little knowledge concerning the effect of micro-politics on workplace learning. The case study took place at the University of Malta and evidence was gained from 35 participants who were undergoing some type of workplace learning, through participant observations and semi-structured interviews. The study employed a qualitative research design and research data was extracted from the fieldwork notes and interview transcriptions of the participants who related the effect of political behaviour they were having (if any) on their learning. A methodology based on an inductivist approach was used to explore the participants’ experiences, thoughts and opinions, since the study involved social processes and behaviours. Collected data which was transcribed and converted to text was analysed by using the NVIVO Qualitative Data Analysis software. The research clearly shows that interpersonal political behaviour may have an intense effect on the employees’ learning, particularly informal learning. The effects can be inhibitive and distressing for some, and supportive and profitable for others, which effects were completely uknown before this research took place. In a minority of cases, workplace politics seemed to have had no effect on individual learning, as some respondents consciously chose to distance and isolate themselves from such behaviours.